Analysis of Student Treatment of 3R Implementation in Waste Management in the Surrounding Environment - Ilahil Riska Dwi Aji Muarifa; Sudarti (Jurnal Multidisiplin Madani, 2023)
Garbage is a complicated problem to solve. As a student, you must understand the impact caused by waste. Therefore, it is necessary to understand how to manage waste properly and correctly so that it does not pollute the environment and has economic value. One way to treat waste that is good and right is to use the 3R method. Waste processing using the 3R method is an innovation in waste treatment that reduces waste piles, the 3R method is reuse, reduce, recycle. Reuse is to reuse waste that is still feasible for the same function or another, reduce is an activity that aims to reduce and prevent waste from arising, and recycle is processing waste into new products. This study used a quantitative method with 70 active student respondents in Physics Education at the University of Jember. From several respondents, the results showed that the majority of students already knew about the processing of the 3R method, but this method was still not optimal in its implementation. Therefore, further understanding is needed so that the environment remains clean and minimizes environmental pollution